2012
DOI: 10.1002/cbdv.201100204
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxonomy of Serbian Teucrium Species Inferred from Essential Oil Chemical Composition: the Case of Teucrium scordium L. ssp. scordioides

Abstract: The volatile constituents of Teucrium scordium L. ssp. scordioides, T. polium, and T. montanum, obtained by hydrodistillation, were investigated by GC-FID and GC/MS analyses. A total of 296 constituents were identified, representing 89.8-98.4% of the oil compositions. The oils of T. polium and T. montanum consisted mainly of sesquiterpenes (64.3 and 72.7%, resp.), with germacrene D (4; 31.0%) and δ-cadinene (10; 8.1%) as the main constituents, respectively. In contrast, the monoterpene menthofuran (1; 11.9%) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…The most abundant compound of the oil was caryophyllene oxide (25.8%), followed by a-pinene (19.4%) and b-pinene (8.5%), whereas among the sesquiterpene hydrocarbons the most representative products were b-sesquiphellandrene (5.9%) and (E)-b-caryophyllene (4.4%). Comparison of our data with the only analysis of the essential oil of this taxa, i.e., from plants collected in Serbia (Radulovi c et al 2012), showed a complete different composition of the oil. In fact, the latter one was characterized by the presence of menthofuran (11.9%), as the main component, and by a complex mixture of fatty acids and fatty acid-derived compounds (39.7%), being both totally absent in the Sicilian accession.…”
Section: Resultsmentioning
confidence: 60%
“…The most abundant compound of the oil was caryophyllene oxide (25.8%), followed by a-pinene (19.4%) and b-pinene (8.5%), whereas among the sesquiterpene hydrocarbons the most representative products were b-sesquiphellandrene (5.9%) and (E)-b-caryophyllene (4.4%). Comparison of our data with the only analysis of the essential oil of this taxa, i.e., from plants collected in Serbia (Radulovi c et al 2012), showed a complete different composition of the oil. In fact, the latter one was characterized by the presence of menthofuran (11.9%), as the main component, and by a complex mixture of fatty acids and fatty acid-derived compounds (39.7%), being both totally absent in the Sicilian accession.…”
Section: Resultsmentioning
confidence: 60%
“…It has been previously noted that the essential oil composition may vary greatly depending on the habitat, location, climatic conditions and soil biology [51] . This varying biospheric condition regulates the internal physiology of the plant to synthesize such diverse array of chemicals within the same species [52] .…”
Section: Essential Oil Compositionmentioning
confidence: 99%
“…Recently, progress in chromatographic/spectral technique and software for automatically analyzing MS data, such as MzMine [6], MathDAMP [7], Tagfinder [8] and MetAlign [9], has remarkably facilitated chemotaxonomy and nontargeted functional genomics research [10], [11]. The former would play an important role in the study of taxonomy and has been used in chemotaxonomy studies of fungi and plants, and is a promising method for those highly hybrid plants and its closely related species, such as Citrus and its related genera [12][14].…”
Section: Introductionmentioning
confidence: 99%